Ice Motion Detector System. Ice Engineering. Number 4, September 1993 - Zufelt, Jon (1993)
This issue describes the design and testing of an ice motion detector system, which was developed to give downstream communities advance warning that an ice cover had broken up and begun moving, in an effort to reduce damages associated with ice runs and jamming. Why Have a Detector System? Ice jams result in more than $125 million in damages annually; much of this sum represents damage to personal property. A significant amount of research has concentrated on the stages associated with ice jams and their frequency of occurrence, as well as methods of ice jam control and flooding reduction. Current research is addressing ice jam formation and jamming location. In areas where ice jamming and flooding present a recurrent threat, measures usually are taken to predict the occurrence of ice jams and to minimize their impact. In these cases, advance warning that an ice run has begun and that flooding is possible could allow downstream communities to evacuate flood-prone areas, close bridges, and mobilize flood fighting efforts in a timely manner. The original document contains color images.